The INNOVATION IN THE USE OF CROSS PUZZLES AS BIOLOGY LEARNING MEDIA TO IMPROVE LEARNING OUTCOMES - Eka Ayu Mulyasari; Rr. Berly LDLH; Indah Rakhmawati Afrida (ScienceEdu, 2023)
In the Merdeka Curriculum, teachers have the flexibility to choose various learning models and media used to create student-centered learning. The purpose of this study was to determine the increase in student learning outcomes in class X biology subject through the Problem Based Learning (PBL) learning model which was integrated with crossword media. This classroom action research consisted of 3 cycles with research subjects being students of XD class SMA Negeri 2 Tanggul for the 2022/2023 academic year. This study focused on learning outcomes. Data obtained through observation and post-test. The results showed that in the first cycle the percentage of successful students achieved a score above or in accordance with the KKM (Minimum Completeness Criteria) was 53%, the second cycle was 58% and in the third cycle was 78%, it can be seen that there was an increase in the percentage from cycle I to cycle II by 5% and cycle II to cycle III there is a percentage increase of 20%. So it can be concluded that the use of the Problem Based Learning (PBL) model that is integrated with crossword media can improve student learning outcomes.